Diversity of Children's Independent Mobility in Dhaka. (November 2019) - Bhuyan, Md Rashed; Zhang, Ye
Children's mobility environment is an ignored topic in discussions of sustainable urbanisation in the Global South. This study explores the independent mobility of children from ages 7 to 15 in Dhaka—reportedly the world's densest urban conglomeration. Surveys and interviews of children ( n = 308) and their parents were conducted in eight schools in Dhaka, located in three strategically selected residential areas. Children's independent mobility (CIM) was then analysed with reference to relevant themes across social profiles of children. The results depict the current state of CIM in Dhaka: 59 per cent of the children experienced a low degree of CIM from school to home. The degree of CIM varied noticeably across study areas, income groups, age and gender groups. The presence of cars in streets was identified as an important barrier for CIM by both children and parents. These results could inform policymakers, transportation planners and urban advocates focussing on creating an inclusive and child-friendly urban environment.